Prevalence De L’anemie Et Des Anticorps Specifiques Anti-P. Falciparum Chez Les PVVIH Et Co-Infectees Par Le Plasmodium Falciparum Au Congo-Brazzaville - S. Judith Gbenoudon Satoguina; Ruphin Bolanga; Etienne Mokondjimobe; Comlan De Souza (European Scientific Journal, ESJ, 2016)
HIV and P. falciparum lead to diseases with overlapping endemic areas. Both diseases are leading cause of nearly 2 millions of deaths each year, which occur mostly in developing countries. People living with HIV are more susceptible to disease progressions. It is therefore important to further understand the biology of HIV and P. falciparum coinfection. The present study sets to characterize the coinfection with regard to malaria specific antibodies and to anemia. We found that antibody and hemoglobin levels as well as CD4 counts differ significantly according to parasite load and to treatment with anti retroviral. People undergoing treatment with antiretroviral, produced specific antimalarial IgG compared to their treatment naïve counterparts.